More adverse events after osteosyntheses compared to arthroplasty in geriatric proximal humeral fractures involving anatomical neck - Porschke, Felix; Bockmeyer, Julia; Nolte, Philip-Christian; Studier-Fischer, Stefan; Gühring, Thorsten; Schnetzke, Marc (Journal of Clinical Medicine, 2021)
The purpose of this study was to compare adverse events and clinical outcomes of geriatric proximal humerus fractures (PHF) involving the anatomical neck (type C according to AO classification) treated with open reduction and internal fixation (ORIF) using locking plate vs. arthroplasty. In this retrospective cohort study, geriatric patients (>64 years) who underwent operative treatment using ORIF or arthroplasty for type C PHFs were included. Complications, revisions and clinical outcomes using Constant Murley Score (CMS) and Disabilities of the Arm, Shoulder and Hand (DASH) Score were assessed and compared between groups. At a mean follow up of 2.7 ± 1.7 years, 59 patients (mean age 75.3 ± 5.5 years) were included. In 31 patients ORIF was performed and 29 patients underwent arthroplasty. Complications and revision surgeries were significantly more frequent after ORIF (32.6% vs. 7.1%, p = 0.023 and 29.0% vs. 7.1%, p = 0.045). In contrast, clinical outcomes showed no significant differences (DASH 39.9 ± 25.7 vs. 39.25 ± 24.5, p = 0.922; CMS 49.7 ± 29.2 vs. 49.4 ± 25.2, p = 0.731). ORIF of type C PHFs in geriatric patients results in significantly more complications and revision surgery when compared to arthroplasty. Therefore, osteosynthesis of geriatric intraarticular fractures of the proximal humerus must be critically evaluated.